ANALISIS HUBUNGAN TIMBAL BALIK ANTARA ESG DISCLOSURE DAN MANAJEMEN LABA (Studi Empiris pada Perusahaan Sektor Nonkeuangan yang Terdaftar di Bursa Efek Indonesia Tahun 2019-2023) - Sabrina Kanza Dewanti; Siti Mutmainah (Diponegoro Journal of Accounting, 2025)
The relationship between ESG disclosure and earnings management requires further exploration so this study aims to examine the relationship of mutual influence. Earnings management is proxied with accrual earnings management (AEM) and real earnings management (REM). The predictor variables used in the study included age of firm, board of commissioner size, firm size, and leverage. The population in this research is the non-financial sector companies listed on the IDX in 2019-2023. Analytical techniques used are the Ordinary Least Square (OLS) and Two-Stage Least Square (2SLS) methods. The results show that a reciprocal relationship occurred between ESG and REM disclosure, while the ESG and AEM disclosure relationship was only unidirectional. ESG disclosure had a significant negative effect on AEM, but AEM did not have a significant influence on ESG disclosure. The simultaneous relationship between ESG and REM disclosure show that ESG and REM disclosure had a significant negative mutual influence.